2004
DOI: 10.1074/jbc.m409732200
|View full text |Cite
|
Sign up to set email alerts
|

An RNA-interacting Protein, SYNCRIP (Heterogeneous Nuclear Ribonuclear Protein Q1/NSAP1) Is a Component of mRNA Granule Transported with Inositol 1,4,5-Trisphosphate Receptor Type 1 mRNA in Neuronal Dendrites

Abstract: mRNA transport and local translation in the neuronal dendrite is implicated in the induction of synaptic plasticity. Recently, we cloned an RNA-interacting protein, SYNCRIP (heterogeneous nuclear ribonuclear protein Q1/NSAP1), that is suggested to be important for the stabilization of mRNA. We report here that SYNCRIP is a component of mRNA granules in rat hippocampal neurons. SYNCRIP was mainly found at cell bodies, but punctate expression patterns in the proximal dendrite were also seen. Time-lapse analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(104 citation statements)
references
References 55 publications
5
99
0
Order By: Relevance
“…Immunoprecipitation from the cell lysate and proteomic analysis of the IRBITinteracting proteins was performed as described (20).…”
Section: Methodsmentioning
confidence: 99%
“…Immunoprecipitation from the cell lysate and proteomic analysis of the IRBITinteracting proteins was performed as described (20).…”
Section: Methodsmentioning
confidence: 99%
“…By mass spectrometry, the complex contained ribosomes and proteins involved in the control of protein synthesis [PABP1 (poly(A)-binding protein) and FMRP], cytoskeletal proteins (tubulins, tau, actin, and internexin), cytoskeleton control proteins (IQGAP1, cdc42, and rac1), motor proteins (dynein, kinesin, and myosin), and proteins normally found in the nucleus such as nucleolin and RNA helicase A (Villacé et al, 2004). Bannai et al (2004) reported that SYNCRIP (heterogenous nuclear ribonuclear protein Q1/NSAP1) was transported bidirectionally within dendrites, at a velocity about equivalent to that of Pur␣-containing granules (Kanai et al, 2004). SYNCRIP colocalized in cultured neurons with Staufen1 and the 3Ј-untranslated region of inositol 1,4,5-triphosphate receptor type 1 mRNA, indicating that it is transported as a component of mRNA granules (Bannai et al, 2004) In Drosophila melanogaster oocytes, oskar mRNA is localized to the posterior pole.…”
Section: Mrna-associated Granules and Kinesin Motorsmentioning
confidence: 99%
“…Bannai et al (2004) reported that SYNCRIP (heterogenous nuclear ribonuclear protein Q1/NSAP1) was transported bidirectionally within dendrites, at a velocity about equivalent to that of Pur␣-containing granules (Kanai et al, 2004). SYNCRIP colocalized in cultured neurons with Staufen1 and the 3Ј-untranslated region of inositol 1,4,5-triphosphate receptor type 1 mRNA, indicating that it is transported as a component of mRNA granules (Bannai et al, 2004) In Drosophila melanogaster oocytes, oskar mRNA is localized to the posterior pole. Localization of oskar depends on the kinesin heavy chain (KIF5) and not the KLC, as shown in a KLC null mutant (Brendza et al, 2000).…”
Section: Mrna-associated Granules and Kinesin Motorsmentioning
confidence: 99%
“…Mammalian SYNCRIP/ hnRNPQ is a component of neuronal RNA transport granules that contain CamKIIα, Arc, and IP3R1 mRNAs (Bannai et al 2004;Kanai et al 2004;Elvira et al 2006) and is thought to regulate translation via an interaction with the noncoding RNA BC200/BC1, itself a translational repressor (Duning et al 2008). Moreover, SYNCRIP/hnRNPQ competes with poly(A) binding proteins to inhibit translation in vitro (Svitkin et al 2013) and regulates dendritic morphology (Chen et al 2012) via association with, and localization of, mRNAs encoding components of the Cdc-42/N-WASP/Arp2/3 actin nucleation-promoting complex.…”
Section: Introductionmentioning
confidence: 99%